Evaluation of electrical conductivity, pH and refractive index as physico-chemical parameters for quality control of Aveloz homeopathic solutions - da Silva, Isabella de Oliveira; Harduim, Rafael Cardoso; Zacharias, Carlos Renato [UNESP]; Garcia, Sheila; Holandino, Carla (My University, 2011)
Euphorbia tirucalli Lineu (Aveloz) belongs to the family Euphorbiaceae and is used in the treatment of cancer and warts. Some studies have reported that phorbol esters are the active principles responsible for the antitumor activity of Aveloz. The production of these molecules occurs in greater quantity in May, during the morning. This study aimed to evaluate whether the physico-chemical parameters of Aveloz homeopathic aqueous solutions such as pH, electrical conductivity and refractive index change due to storage time. Such parameters were measured regularly for 180 days. All solutions were prepared according to the method of grinding with lactose and subsequent dissolution in aqueous medium, as described in the Brazilian Homeopathic Pharmacopoeia, using as starting point the Aveloz latex collected in May. Homeopathic aqueous solutions containing only lactose were also prepared and evaluated as a control group. The potencies that were analyzed for electrical conductivity, pH and refractive index were: 4cH, 7cH, 9cH, 12cH, 14cH, 15cH, 29cH, 30cH. As a result, we found out that there was only statistical difference (p=0.035) in electrical conductivity between the homeopathic solutions containing Aveloz and the homeopathic solutions without Aveloz, when 15cH potency was compared. We also observed that the electrical conductivity increased with the aging of the solutions but is not directly related to the pH or the refractive index of the solutions, indicating that the aging process may alter the electrical conductivity of the homeopathic medicines. The presence of gas inside the glass that stores these solutions may affect the electrical conductivity measurements. Finally, no statistically significant difference was observed (p> 0.05) in the pH and refractive index.
Keywords: Aveloz; Electrical conductivity; Homeopathy; pH; Refractive index